Axially vascularized tissue-engineered bone constructs retain their in vivo angiogenic and osteogenic capacity after high-dose irradiation - Eweida, Ahmad; Giordano, Frank Anton; Fleckenstein, Jens; Wenz, Frederik; Brockmann, Marc Alexander; Harhaus-Wähner, Leila (Journal of tissue engineering and regenerative medicine, 2018)
In order to introduce bone tissue engineering to the field of oncological reconstruction, we are investigating for the first time the effect of various doses of ionizing irradiation on axially vascularized bone constructs. Synthetic bone constructs were created and implanted in 32 Lewis rats. Each construct was axially vascularized through an arteriovenous loop made by direct anastomosis of the saphenous vessels. After 2 weeks, the animals received ionizing irradiation of 9 Gy, 12 Gy and 15 Gy, and were accordingly classified to groups I, II and III, respectively. Group IV was not irradiated and acted as a control. Tissue generation, vascularity, cellular proliferation and apoptosis were investigated either 2 or 5 weeks after irradiation through micro-computed tomography, histomorphometry and real-time polymerase chain reaction (PCR). At 2 weeks after irradiation, tissue generation and central vascularity were significantly lower and apoptosis was significantly higher in groups II and III than group IV, but without signs of necrosis. Cellular proliferation was significantly lower in groups I and II. After 5 weeks, the irradiated groups showed improvement in all parameters in relation to the control group, indicating a retained capacity for angiogenesis after irradiation. PCR results confirmed the expression of osteogenesis-related genes in all irradiated groups. Dense collagen was detected 5 weeks after irradiation, and one construct showed discrete islands of bone indicating a retained osteogenic capacity after irradiation. This demonstrates for the first time that axial vascularization was capable of supporting a synthetic bone construct after a high dose of irradiation that is comparable to adjuvant radiotherapy. Copyright © 2016 John Wiley & Sons, Ltd.